Toward a comprehensive understanding of textiles functionalized with silver nanoparticles. Issue 8 (31st March 2019) - Syafiuddin, Achmad
Abstract : This article provides a comprehensive understanding of development of textiles functionalized with silver nanoparticles (AgNPs). There are three established methods to fabricate textiles functionalized with AgNPs, namely, solution‐immersion, layer‐by‐layer deposition, and sonochemical. In addition, several textile types such as cotton, wool, polyester, silk, cotton/polyester blend, polyamide, and regenerated cellulose have been used for the fabrication. The AgNP deposition mechanism on textiles is mainly due to electrostatic interaction between AgNPs and textile constituents. It was exhibited that the deposition of AgNPs on textiles can transform their textiles colors. In addition, it was demonstrated that the deposition of AgNPs on textiles is not permanent, particularly against washing treatment. Textiles modified with AgNPs have several promising applications such as antibacterial, antifungal, catalyst, electronic devices, water treatment, sun protection, air treatment, and surface‐enhanced Raman scattering, which are comprehensively discussed in this article. Future challenges in fabricating textiles functionalized with AgNPs remain on how this can be carried out to improve long‐term stabilization of AgNPs on textiles to achieve their permanent deposition by employing greener approaches. Abstract : This article provides a comprehensive understanding of development of textiles functionalized with silver nanoparticles (AgNPs). There are three established methods to fabricate textiles functionalized with AgNPs, namely, solution‐immersion, layer‐by‐layer deposition, and sonochemical. Future challenge in fabricating textiles functionalized with AgNPs remains on how this can be carried out to improve long‐term stabilization of AgNPs on textiles to achieve their permanent deposition by employing greener approaches.